The influence of e-commerce trust and e-commerce satisfaction to customer loyalty on Sociolla application users - Jesicha Chanhwa; Rahmiati (Universitas Negeri Padang, 2021)
This research aims to analyze (1) the influence of e-commerce trust on customer loyalty on Sociolla online shopping application users. (2) The effect of e-commerce satisfaction on customer loyalty on Sociolla online shopping application users. The population in the study was all users of the online shopping app Sociolla and the sample in this study is Sociolla users who had shopped more than once. The number of samples in this study was 285 respondents. Data was collected through online questionnaire dissemination and data processing is collected through SPSS software. The results of this study showed that (1) e-commerce trust has a positive and significant effect on customer loyalty in Sociolla online shopping application users. (2) e-commerce satisfaction positively and significantly affects customer loyalty in Sociolla online shopping application users.